DNA Retention of Child Offenders in Malaysia: Implications on the Basic Rights of Children: (Penyimpanan DNA Pesalah Kanak-kanak di Malaysia: Penilaian Semula Hak Asasi Kanak-kanak) (Kanun: Jurnal Undang-undang Malaysia, 2017)
The use of DNA evidence has facilitated the criminal justice process, as a tool for the purpose of preventing and solving crimes. The history of the establishment of the DNA data bank has shown the use of DNA evidence to be very significant in most countries, including Malaysia. This article will discuss the issues relating to the retention of DNA in the Malaysian Forensic DNA data bank by focusing on the aspects of privacy rights, type of offence, and the time limit for storage of child offenders' DNA in the context of Malaysian law. Apart from that, the study shows that the retention of child offenders' DNA without a time limit is against the principle "in the best interest of the child" Article 3 of the Convention on the Rights of the Child (CRC), as it undermines the child's basic rights.Keywords: The Deoxyribonucleic Acid (DNA) Identification Act of 2009, DNA retention, crime, privacy, child